Biogas Production from the Degradation of Biodiesel Agroindustry Waste - Lyra Corrêa, Christiane; Fritz, Natally; Firmo, Alessandra; Jucá, José Fernando (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Due to advances in environmental policies in Brazil and demand to reach knowledge and techniques of new ways for obtaining energy, to avoid future blackouts and rationing, the renewable energy market is on the rise, and biofuel is a very promising energy source. In the biodiesel agro-industries, there is a constant increase in the residues generation (glycerin, washing waters, press cake, and oil sludge) resulted from the fuel production process, so there is the need for residues management or treatment valuing biodiesel by-products. In this paper, it was evaluated the main types of waste generated at the Caetés Biodiesel Pilot Plant - BR and analyzed the biogas generation potential of this waste. In the laboratory, comparative analyses were carried out between different combinations and percentages of sludge (inoculum containing a high concentration of methanogenic microorganisms to accelerate biomass degradation process) and biodiesel by-products. It was investigated through tests of Biochemical Methane Potential (BMP) biogas generation from samples and simulated the capacity of electric power generation. Based on these data and the calculation of energy efficiency, it can be suggested the use of biodigesters with residues generated in the plant to produce energy in the unit enabling a 20% reduction in power consumption.